A Literature Review on Mathematical Morphology Based Image Segmentation Techniques - Pinaki Pratim Acharjya; Subhabrata Barman; Subhankar Joardar; Santanu Koley (Recent Progress in Science and Technology Vol. 8, 2023)
Digital image processing is an emerging technology and has found vast applications in biomedical imaging, stellar imaging, remote sensing and radar imaging, the study of climatology, seismology, seabed studies and exploration of earth resources. Image segmentation process of any digital image has been found important in the second level of processing and the main aim of this level of processing is to generate and feed the information to the computer machine for subsequent higher level image processing. Morphology based image segmentation has occupied a significant position in state of art image processing and it needs a thorough investigation for the betterment of the subject concerned and for the ease of handling of the massive data by the machines. The present chapter has aimed at to present a thorough and exhaustive literature study on various aspects of segmentation of digital images using morphological approach.